Factors of Decreasing Learning Outcome in Islamic Religious Education During Covid-19 Pandemic at State Elementary School: A Study to Psychomorical Domain - Fajri Ismail (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The limited face to face learning policy implemented by the Indonesian government during the COVID-19 pandemic has received two forms of resistance: closed (practiced by teachers, parents, and students) and open (practiced by teachers). This resistance has made it difficult to resume face-to-face learning. As such, this article seeks to illustrate the public's resistance to the face to face policy and analyze the implications of this resistance in Madrasah Ibtidaiyah Islami. This article relies on data collected from online media as well as interviews with representatives of diverse elements of society.It shows that resistance has been rooted in several factors: familiarity with online learning, concern that health protocols would not be optimally implemented; and economic concerns. This article recommends conducting further research to obtain a deeper and more comprehensive understanding of the public's resistance to face to face.